Single-Cell Transcriptomic Analysis Reveals Developmental Relationships and Specific Markers of Mouse Periodontium Cellular Subsets - Nagata, Mizuki; Chu, Angel Ka Yan; Ono, Noriaki; Welch, Joshua D.; Ono, Wanida (Frontiers in Dental Medicine, 2021)
The periodontium is essential for supporting the functionality of the tooth, composed of diversity of mineralized and non-mineralized tissues such as the cementum, the periodontal ligament (PDL) and the alveolar bone. The periodontium is developmentally derived from the dental follicle (DF), a fibrous tissue surrounding the developing tooth bud. We previously showed through in vivo lineage-tracing experiments that DF contains mesenchymal progenitor cells expressing parathyroid hormone-related protein (PTHrP), which give rise to cells forming the periodontal attachment apparatus in a manner regulated by autocrine signaling through the PTH/PTHrP receptor. However, the developmental relationships between PTHrP+ DF cells and diverse cell populations constituting the periodontium remain undefined. Here, we performed single-cell RNA-sequencing (scRNA-seq) analyses of cells in the periodontium by integrating the two datasets, i.e. PTHrP-mCherry+ DF cells at P6 and 2.3kb Col1a1 promoter-driven GFP+ periodontal cells at P25 that include descendants of PTHrP+ DF cells, cementoblasts, osteoblasts and periodontal ligament cells. This integrative scRNA-seq analysis revealed heterogeneity of cells of the periodontium and their cell type-specific markers, as well as their relationships with DF cells. Most importantly, our analysis identified a cementoblast-specific metagene that discriminate cementoblasts from alveolar bone osteoblasts, including Pthlh (encoding PTHrP) and Tubb3. RNA velocity analysis indicated that cementoblasts were directly derived from PTHrP+ DF cells in the early developmental stage and did not interconvert with other cell types. Further, CellPhoneDB cell-cell communication analysis indicated that PTHrP derived from cementoblasts acts on diversity of cells in the periodontium in an autocrine and paracrine manner. Collectively, our findings provide insights into the lineage hierarchy and intercellular interactions of cells in the periodontium at a single-cell level, aiding to understand cellular and molecular basis of periodontal tissue formation.